RELASI PEMILIKAN RAKYAT DAN NEGARA ATAS TANAH PERSPEKTIF HUKUM PERTANAHAN ISLAM DAN HUKUM PERTANAHAN INDONESIA - Ridwan Ridwan (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2011)
Land ownership according to Islamic Jaw and Indonesia agrarian law is law characteristic of communalistic-theistic-selective. People ownership law concept upon land in Indonesia agrarian law that is law number 5 o f the year I960 (UUPA) and Islamic law has an equality on basis philosophical or basis of law is to create land ownership system fairly and smoothly based on equality inf front of law based on religious spiritual value.